Impaired tricarboxylic acid cycle flux and mitochondrial aerobic respiration during isoproterenol induced myocardial ischemia is rescued by bilobalide - Zhe Wang; Fan Zhang; Wei Liu; Ning Sheng; Hua Sun; Jinlan Zhang (Elsevier, 2021)
There is an urgent need to elucidate the pathogenesis of myocardial ischemia (MI) and potential drug treatments. Here, the anti-MI mechanism and material basis of Ginkgo biloba L. extract (GBE) were studied from the perspective of energy metabolism flux regulation. Metabolic flux analysis (MFA) was performed to investigate energy metabolism flux disorder and the regulatory nodes of GBE components in isoproterenol (ISO)-induced ischemia-like cardiomyocytes. It showed that [U-13C] glucose derived m+2 isotopologues from the upstream tricarboxylic acid (TCA) cycle metabolites were markedly accumulated in ISO-injured cardiomyocytes, but the opposite was seen for the downstream metabolites, while their total cellular concentrations were increased. This indicates a blockage of carbon flow from glycolysis and enhanced anaplerosis from other carbon sources. A Seahorse test was used to screen for GBE components with regulatory effects on mitochondrial aerobic respiratory dysfunction. It showed that bilobalide protected against impaired mitochondrial aerobic respiration. MFA also showed that bilobalide significantly modulated the TCA cycle flux, reduced abnormal metabolite accumulation, and balanced the demand of different carbon sources. Western blotting and PCR analysis showed that bilobalide decreased the enhanced expression of key metabolic enzymes in injured cells. Bilobalide's efficacy was verified by in vivo experiments in rats. This is the first report to show that bilobalide, the active ingredient of GBE, protects against MI by rescuing impaired TCA cycle flux. This provides a new mechanism and potential drug treatment for MI. It also shows the potential of MFA/Seahorse combination as a powerful strategy for pharmacological research on herbal medicine.